Karakter Visual pada Video Promosi Sebagai Upaya Memperkenalkan UKM Sidoarjo - Aphief Tri Artanto; Fatimatul Zuhroh; Aryo Bayu Wibisono (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2018)
To improve the image of UMKM (Usaha Mikro Kecil dan Menengah) villages in Sidoarjo district to introduce the advantages possessed by Sidoarjo UMKM , through video media as a supporter of the Sidoarjo Regency program. With the preparation of this journal, it is expected that the UMKM s of Sidoarjo Regency will have a video character that will be used for the purposes of the promotion of UMKM s in Sidoarjo Regency to gain a wider market share. Data mining carried out observations on 12 leading UMKM villages in Sidoarjo district. Methods of data collection using qualitative and quantitative methods, namely observation, interviews, and questionnaires. In designing promotional videos SWOT analysis, framing analysis, domain analysis and research through questionnaires are used, which are the basis for the promotion of video promotion to be able to meet the target segment target. Keyword : Promotion Video, UMKM Promotion Video, Sidoarjo UMKM